Sleep Quality in Children and Adults with Rett Syndrome - Leven, Y.; Wiegand, F.; Wilken, B. (Neuropediatrics, 2020)
Background Over 80% of individuals suffering from Rett syndrome (RTT) are affected over their life period by sleeping disorders. Little is known about the impact of those on the quality of life and a clinical approach to the treatment of sleep disturbances is lacking.Aims Primary aim was to assess sleep quality in children and adults. Secondary aim was to assess behavioral disorders and their relationship to sleep quality. The medication taken by the subjects was also included.Methods Sleep quality and medication were assessed using the sleeping questionnaire for children with neurological and other complex diseases (SNAKE). Behavioral disorders were assessed by the Rett Syndrome Behavior Questionnaire (RSBQ). Questionnaires were sent to the 700 members of the Elternhilfe für Kinder mit Rett Syndrom in Deutschland e.V. (Rett Aid) of which 287 were included. Questionnaires were filled out by the primary caregivers.Results Sleep quality was rated as very good to good by over 60% of caregivers in contrast to data available in the literature. Behavioral disorders related to regression such as loss of acquired hand skills (p = 0.046) and isolation (p = 0.002) were found to be associated with sleep quality. Melatonin showed a significant association (p = 0.007) with sleep quality.Conclusion Our study showed sleep dysfunction to be less prevalent in RTT-affected individuals than evidence from past studies has suggested. Nevertheless, this remains a subjective assessment of sleep quality and therefore the need to find objective, disorder-specific parameters that measure sleep quality in RTT patients persists.
Keywords: Rett syndrome; quality of life; sleep quality; SNAKE; RSBQ; MECP2